PERAN GURU DALAM MENINGKATKAN PEMBELAJARAN DI SMPN 17 MAKASSAR - Suarga, Suarga; Amalia, Reski; Nanda, Nanda; Fadil, Anugrah (Department of Islamic Education Management, 2026)
This study aims to examine in depth the various roles of teachers, such as strategy designers, classroom managers, and motivators, in efforts to improve learning at SMPN 17 Makassar. This study used a descriptive qualitative approach with one teacher at SMPN 17 Makassar who was selected purposively. Data were collected through interviews and analyzed descriptively to examine learning planning and implementation, teaching strategies, and obstacles and supporting factors faced by teachers. The results show that teachers carry out learning planning systematically, beginning with reviewing the curriculum and Learning Objectives Flow (ATP). In implementation, teachers apply various learning models such as Problem Based Learning, Project Based Learning, Discovery Learning, and differentiated learning, utilizing digital technology and conducting regular formative assessments to monitor student understanding. The main obstacles faced are the diversity of abilities and low learning motivation of some students, but this is supported by the role of the principal, colleagues, and the availability of infrastructure. The implication of this study is that the findings of teacher best practices at SMPN 17 Makassar can serve as an important guide for formulating school policies and teacher training programs in the future.